2015
DOI: 10.1038/leu.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Imprinted genes in myeloid lineage commitment in normal and malignant hematopoiesis

Abstract: Genomic imprinting is characterized by the parent-of-origin monoallelic expression of several diploid genes because of epigenetic regulation. Imprinted genes (IGs) are key factors in development, supporting the ability of a genotype to produce phenotypes in response to environmental stimuli. IGs are highly expressed during prenatal stages but are downregulated after birth. They also affect aspects of life other than growth such as cognition, behavior, adaption to novel environments, social dominance and memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 146 publications
(147 reference statements)
0
10
0
Order By: Relevance
“…Finally, in our previous work we demonstrated that very small embryonic-like stem cells, which share several markers with migrating PGCs and express SexH receptors, can become specified into HSPCs [8,45,[53][54][55]. Whether some leukemias could originate in these developmentally primitive cells was recently hypothesized by another group, but requires further study [56].…”
Section: Discussionmentioning
confidence: 78%
“…Finally, in our previous work we demonstrated that very small embryonic-like stem cells, which share several markers with migrating PGCs and express SexH receptors, can become specified into HSPCs [8,45,[53][54][55]. Whether some leukemias could originate in these developmentally primitive cells was recently hypothesized by another group, but requires further study [56].…”
Section: Discussionmentioning
confidence: 78%
“…Finally, in our previous work we demonstrated that very small embryonic-like stem cells, which share several markers with migrating PGCs and express SexH receptors, can become specified into HSPCs [ 8 , 45 , 53 55 ]. Whether some leukemias could originate in these developmentally primitive cells was recently hypothesized by another group, but requires further study [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…These regions, known as differentially methylated regions (DMRs), exhibit unique patterns of methylation at CG cytosine residues based on the parental origin of the chromosome. The temporo-spatial dosage of imprinted genes governed by genomic imprinting is integral to proper growth and development, and its dysregulation is found in several developmental abnormalities [2] and malignancies such as leukemia [3].…”
Section: Introductionmentioning
confidence: 99%